المسؤولية الاجتماعية وانعكاسها على تعزيز الأداء التسويقي المصرفي: دراسة تحليلية في بعض فروع المصارف التجارية - علي، علي محمود; حسون، ليلي ناصر (جامعة الكوفة - كلية الإدارة والاقتصاد, 2024)
الغرض: يهدف البحث إلى تحديد طبيعة علاقة التأثير والارتباط بين المتغير المستقل (المسؤولية الاجتماعية) والمتغير التابع (الأداء التسويقي) وذلك بتحليل أراء عينة من العاملين في بعض المصارف التجارية في محافظة النجف الأشرف. مجتمع وعينة البحث: يتمثل مجتمع البحث بالعاملين في القطاع المصرفي وتم اختيار عينة قصدية تتكون من (120) عاملا في المصارف المبحوثة يمثل معظمهم شاغلي المواقع الإدارية العليا والوسطى في بعض فروع المصارف الحكومية المتمثلة بمصرف الرافدين والرشيد والمصرف العراقي للتجارة في محافظة النجف ، والاستبيانات الصالحة للتحليل كانت (107) استبانة. الأداة والأساليب الإحصائية المستخدمة في البحث : تم اعتماد استمارة الاستبيان كأداة لجمع البيانات من العينة المقصودة في المصارف التجارية المبحوثة ، كذلك تم استخدام مجموعة من الأساليب الإحصائية لتحليل البيانات المتحصل عليها بهدف التحقق من صحة الفرضيات ، وباستخدام برامج حاسوبية مثل (SPSS v.23) المساهمة العلمية : جاء البحث الحالي ليسد فجوة معرفية تمثلت بقلة الدراسات العربية والأجنبية التي تناولت العلاقة والتأثير بين متغيرات البحث في مخطط فرضي واحد ، وأهمية هذه العلاقة في التميز والتفوق في المصارف عينة البحث. اهم الاستنتاجات: تمتلك المصارف المبحوثة برامج مسؤولية اجتماعية بدرجة متوسطة ، كما وتبين أن الأداء التسويقي المؤشر الأساسي الذي يسهم في استمرار عمل المصرف وبقاؤه في ظل بيئة غير مستقرة ، فالأداء التسويقي يبين للإدارة ما اذا كانت أهداف المصرف تسير على وفق الشكل المخطط له. Purpose: The research aims to determine the nature of the relationship of influence and correlation between the independent variable (social responsibility) and the dependent variable (marketing performance) by analyzing the opinions of a sample of employees in some commercial banks in the Al-Najaf Governorate. Research population and sample: The research population is represented by workers in the banking sector, and a purposive sample was chosen consisting of (120) workers in the researched banks, most of whom represent the occupants of senior and middle administrative positions in some branches of government banks, represented by Al-Rafidain and Al-Rasheed Banks and the Iraqi Trade Bank in Najaf Governorate, and questionnaires suitable for analysis. There were (107) questionnaires. The statistical tool and methods used in the research: The questionnaire form was adopted as a tool for collecting data from the intended sample in the commercial banks investigated. A set of statistical methods were also used to analyze the data obtained with the aim of verifying the validity of the hypotheses, using computer programs such as (SPSS v.23). Scientific contribution: The current research came to fill a knowledge gap represented by the lack of Arab and foreign studies that dealt with the relationship and influence between the research variables in a single hypothetical scheme, and the importance of this relationship in excellence and superiority in the banks sample of the research. The most important conclusions: The investigated banks have social responsibility programs to a moderate degree. It also turns out that marketing performance is the basic indicator that contributes to the continuation of the bank’s work and its survival in an unstable environment. Marketing performance shows management whether the bank’s objectives are proceeding according to the planned format.
Keywords: تحسين الأداء -- إدارة الجودة الشاملة -- المؤسسات الاقتصادية -- الأداء التنظيمي